Children as Victims of Sexual Abuse: Has the Law Provided Enough Justice? - Sigma Febby Annisa (The Indonesian Journal of International Clinical Legal Education, 2020)
The case of child sexual abuse continues to increase over time. Crimes of sexual violence against children are an example of the vulnerability of a child's position, especially for sexual purposes. The image of a child who has been placed as a sexual object has far-reaching implications for a child's life, so she must always face violence, coercion, and physical and psychological violence. Children have basic human rights, like adults, protection of children's rights is not many people come to think and do concrete steps. Therefore, an attempt to protect the rights of children violated by adults, families, and their own environment, even bias so its own parents (adoptive parents / stepparents) and neglect of parents who are less supervising the baby, resulting in an undesirable thing. Criminality is all forms of speech, behavior and behavior that harm society and attack the safety of citizens, both those covered by law and those not yet covered by the criminal law. In carrying out the guidance and protection of children need the role of society through institutions and organizations.